Implementasi Program MADAM JAHERA dalam Menurunkan Tekanan Darah dan Mengatasi Rematik Pada Lansia - Febriana, Annisa; Yunara, Yulia; Rahmah, Laksmi Maliha; Melania, Maria (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2025)
Hypertension and rheumatism are common health problems in the elderly that have an impact on decreasing quality of life and increasing dependence on long-term medication. In the working area of ​​Sungai Ulin Health Center, many elderly people experience high blood pressure and joint pain with low awareness and ability to carry out herbal-based independent therapy. The MADAM JAHERA (Let's Soak Feet with Ginger for Hypertension and Rheumatism) program aims to improve the knowledge and skills of the elderly in implementing foot soak therapy with warm ginger as an alternative management of hypertension and rheumatism. Activities include health checks, counseling, making ginger soaks, and therapy demonstrations. The activity partner is the Elderly Posyandu under the coordination of Sungai Ulin Health Center with 25 participants. Evaluation was carried out through pre-post tests and blood pressure measurements. The results showed an increase in knowledge of 25% (from 60% to 85%), a decrease in systolic blood pressure of 7-27 mmHg, diastolic 6-10 mmHg, and a positive response in the form of a sense of comfort and relaxation. This program is effective in increasing the capacity of the elderly to manage hypertension and rheumatism independently and economically.